2020
DOI: 10.1371/journal.pone.0234547
|View full text |Cite|
|
Sign up to set email alerts
|

The genetic risk for hypertension is lower among the Hungarian Roma population compared to the general population

Abstract: Estimating the prevalence of cardiovascular diseases (CVDs) and risk factors among the Roma population, the largest minority in Europe, and investigating the role of genetic or environmental/behavioral risk factors in CVD development are important issues in countries where they are significant minority. This study was designed to estimate the genetic susceptibility of the Hungarian Roma (HR) population to essential hypertension (EH) and compare it to that of the general (HG) population. Twenty EH associated SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Table 3 shows that regarding data defined by the questionnaire-based survey, as well as by laboratory and physical examinations and used in IR and MetS calculations, significant differences were observed in the average HDL-C concentration and systolic blood pressure; both values were significantly lower in the HR population than in the HG population (1.26 mmol/L vs. 1.37 mmol/L, 123.7 mmHg vs. 126.8 mmHg, respectively). In the case of these two parameters, significant differences were observed in subgroups without and with MetS in harmony with our previous findings on the genetic background of the high prevalence of low HDL-C concentration [ 20 ] and low prevalence of hypertension [ 60 ] among Roma in comparison with the HG population. The prevalence rates of antidiabetic and lipid-lowering therapies were significantly higher among the HR population (11.1% vs. 6.1%, 11.7% vs. 6.8%, respectively), while no significant difference was found in any of the other parameters between the study groups.…”
Section: Resultssupporting
confidence: 89%
“…Table 3 shows that regarding data defined by the questionnaire-based survey, as well as by laboratory and physical examinations and used in IR and MetS calculations, significant differences were observed in the average HDL-C concentration and systolic blood pressure; both values were significantly lower in the HR population than in the HG population (1.26 mmol/L vs. 1.37 mmol/L, 123.7 mmHg vs. 126.8 mmHg, respectively). In the case of these two parameters, significant differences were observed in subgroups without and with MetS in harmony with our previous findings on the genetic background of the high prevalence of low HDL-C concentration [ 20 ] and low prevalence of hypertension [ 60 ] among Roma in comparison with the HG population. The prevalence rates of antidiabetic and lipid-lowering therapies were significantly higher among the HR population (11.1% vs. 6.1%, 11.7% vs. 6.8%, respectively), while no significant difference was found in any of the other parameters between the study groups.…”
Section: Resultssupporting
confidence: 89%
“…Moreover, previous studies provided robust evidence that the high prevalence of smoking behaviours and nicotine dependence was related to genetic susceptibility [ 20 , 21 , 22 ]. Recent studies have shown that the majority of risk alleles of selected non-communicable diseases have been accumulated in the Roma population [ 18 , 23 ], which support the hypothesis that the health status of Roma is determined by a complex set of inheritable factors.…”
Section: Introductionmentioning
confidence: 78%
“…A study, conducted on UK individuals aimed to determine the influences of Body Mass Index (BMI) on smoking habits and intensity, suggests that higher adiposity has a strong influence on smoking behaviours and also associated with smoking initiation at younger ages [ 17 ]. Among Roma population, a shift from traditional lifestyles characterized by higher caloric intakes and more sedentary lifestyle could lead change in BMI distribution, with obesity becoming significantly more common in the younger Roma population [ 12 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that obesity [ 12 , 13 ] and T2DM [ 14 ] are mainly determined by the environment and not by genetic factors, while there are clearly genetic reasons behind the prevalence of elevated blood pressure [ 15 ], low HDL-C levels [ 16 , 17 , 18 ] and age of onset for T2DM [ 19 ] in the Hungarian general population.…”
Section: Introductionmentioning
confidence: 99%